2006
DOI: 10.1165/rcmb.2005-0205oc
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Epithelial Cells Secrete Chemokines in Response to IL-1β and Lipopolysaccharide but Not to Ozone

Abstract: Ozone exposure produces acute inflammation and neutrophil influx in the distal lung. Alveolar epithelial cells cover a large surface area, secrete chemokines, and may initiate or modify the inflammatory response. The effect of ozone on chemokine production by these cells has not been defined. Isolated rat type II cells were cultured in different conditions to express the morphologic appearance and biochemical markers for the type I and the type II cell phenotypes. These cells were exposed to ozone at an air/li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…As shown in Fig. 6, when rat type II cells are cultured on plastic for 2 and 4 days, the expression of LPCAT and SP-A (a type II cell marker) decreased, whereas the expression of T1␣ increased (16). These results strongly suggest that LPCAT is involved with surfactant production and not general membrane biogenesis.…”
Section: Kgf Increases Lpcat Expression In Cultured Adultmentioning
confidence: 81%
See 1 more Smart Citation
“…As shown in Fig. 6, when rat type II cells are cultured on plastic for 2 and 4 days, the expression of LPCAT and SP-A (a type II cell marker) decreased, whereas the expression of T1␣ increased (16). These results strongly suggest that LPCAT is involved with surfactant production and not general membrane biogenesis.…”
Section: Kgf Increases Lpcat Expression In Cultured Adultmentioning
confidence: 81%
“…Rat alveolar type II cells were isolated and cultured as described (15,27). A type I-like cell phenotype was generated by culturing type II cells on plastic dishes in DMEM plus 10% FBS without KGF (16). Freshly isolated mouse alveolar type II cells were isolated from adult C57BL͞6 mice as described (28).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies in vitro, we found that exposure to ozone induces toxicity in alveolar epithelial cells but without a substantial increase in chemokine production (8)(9)(10). Isolated human alveolar macrophages and THP-1 cells derived from monocytic leukemic cells also fail to secrete chemokines in response to ozone (11,12).…”
mentioning
confidence: 87%
“…Alveolar type II cells were isolated from pathogen-free adult male Sprague-Dawley rats (Harlan, Indianapolis, IN) by dissociation with porcine pancreatic elastase (Roche Molecular Biochemicals, Indianapolis, IN) and partial purification on discontinuous density gradients by standard methods (10,17). Type II cells were plated on 6-well tissue culture plastic plates.…”
Section: Rat Alveolar Epithelial Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation